Impacts of historical and projected climate changes on ice surfaces of the Tibbitt to Contwoyto Winter Road, Northwest Territories, Canada - Zell, Erika (University of Waterloo, 2014)
Seasonal ice and winter roads are a historically important part of the Canadian arctic transportation network. Constructed over frozen lakes, rivers, permafrost zones, and seasonally frozen ground, the roads service rural and aboriginal communities and resource extraction projects which are otherwise fly-in only for the rest of the year. The Tibbitt to Contwoyto Winter Road (TCWR) is one of the most economically significant and heavily used roads, running from outside of Yellowknife, Northwest Territories, to Contwoyto Lake, Nunavut, connecting three of Canada’s largest diamond mines, with a fourth project set to open on route by 2017. The TCWR has been constructed annually since 1982 as a joint venture between mine operators Diavik Diamond Mines Inc., BHB Billiton Diamonds Inc., and DeBeers Canada Inc., and requires a minimum ice thickness of 0.7 m to begin operations, with an average open season of 67 days. Current projections suggest an arctic amplification of the global climate warming signal, as well as changes to arctic precipitation patterns. Both have the potential to alter lake ice conditions, with economic impacts for the long-term viability of ice roads for moving mine supplies north via land. This thesis uses a one-dimensional thermodynamic lake ice model (Canadian Lake Ice Model – CLIMo), forced with atmospheric reanalysis data (ERA-Interim) to simulate historical ice conditions, as well as regional climate model outputs (Canadian Regional Climate Model – CRCM 4.2.0), to make near-future projections for ice phenology and thickness trends. Using road opening and closing dates provided by road managers, we model the historical variability in ice phenologies for the known operations period 1982-2011, as well as future conditions for the period 2041-2070 compared against a 1961-1990 baseline for a future climate scenario based on IPCC SRES scenario A2. Model runs suggest that climatic changes in the arctic, primarily warming surface air temperatures, could pose a threat to continued operations of the ...